IDENTIFICATION OF POTENTIAL STUDY OF CULTURAL HERITAGE ON CHINESE COIN FINDINGS IN BANYUWANGI DISTRICT: IDENTIFIKASI KAJIAN POTENSI CAGAR BUDAYA PADA TEMUAN KOIN CHINA DI KABUPATEN BANYUWANGI - miskawi; agus mursidi; Abdul Shomad (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Many Chinese coins are found in Banyuwangi district with various variations. The purpose of this study was to identify the findings of Chinese coins in Setembel hamlet, Gambiran village, Banyuwangi district. The formulation of the problem is how to identify findings of Chinese coins?, and what is the history of dynasties in Chinese coins in Banyuwangi. The method used is a qualitative method using the Magnifying Plus Application, the Pleco Android Application and Chinese Handwriting Recognizing. Research results Identification Results Of the 76 samples of Chinese coins that can be identified and classified based on the ruling dynasty and kings in China, 52 pieces were identified, 24 pieces were illegible due to wear and tear. Based on the above classification, the most commonly found in Banyuwangi are Chinese products from the Song dynasty, 80% and 20% from the Ming dynasty.